Impact of gastric emptying on the pharmacokinetics of ethanol as influenced by cisapride - Kechagias, S (Blackwell Science Inc, 1999)
AIMS: To examine the influence of cisapride on the pharmacokinetics of ethanol and the impact of gastric emptying monitored by the paracetamol absorption test. METHODS: Ten healthy male volunteers took part in a cross-over design experiment. They drank a moderate dose of ethanol 0.30 g kg(−1) body weight exactly 1 h after eating breakfast either without any prior drug treatment or after taking cisapride (10 mg three times daily) for 4 consecutive days. In a separate study, the same dose of ethanol was ingested on an empty stomach (overnight fast). Paracetamol (1.5 g) was administered before consumption of ethanol to monitor gastric emptying. Venous blood was obtained at 5–10 min intervals for determination of ethanol by headspace gas chromatography and paracetamol was analysed in serum by high performance liquid chromatography (h.p.l.c.). RESULTS: The maximum blood-ethanol concentration (C(max)) increased from 3.8±1.7 to 5.6±2.3 mmol l(−1) (±s.d.) after treatment with cisapride (95% confidence interval CI on mean difference 0.28–3.28 mmol l(−1)). The area under the blood-ethanol curve (AUC) increased from 6.3±3.5 to 7.9±2.6 mmol l(−1) h after cisapride (95% CI −0.74–3.9 mmol l(−1) h). The mean blood ethanol curves in the cisapride and no-drug sessions converged at ≈2 h after the start of drinking. Both C(max) and AUC were highest when the ethanol was ingested on an empty stomach (C(max) 9.5±1.7 mmol l(−1) and AUC 14.6±1.9 mmol l(−1) h), compared with drinking 1 h after a meal and regardless of pretreatment with cisapride. CONCLUSIONS: A small but statistically significant increase in C(max) occurred after treatment with cisapride owing to faster gastric emptying rate as shown by the paracetamol absorption test. However, the rate of absorption of ethanol, as reflected in C(max) and AUC, was greatest after drinking the alcohol on an empty stomach. The cisapride–ethanol interaction probably lacks any clinical or forensic significance.